Long-Term Outcomes of Successful Revascularization for Patients With Coronary Chronic Total Occlusions: A Report of 1,655 Patients - Guo, Lei; Zhang, Xiaoyan; Lv, Haichen; Zhong, Lei; Wu, Jian; Ding, Huaiyu; Xu, Jiaying; Zhou, Xuchen; Huang, Rongchong (Frontiers in Cardiovascular Medicine, 2020)
Background: To date, the benefit of successful revascularization of chronic total occlusions (CTOs) on prognosis remains uncertain and there is a paucity of data on the impact of successful revascularization for CTO patients on long-term cardiovascular survival. This study aimed to investigate the long-term cardiovascular survival for patients with successful and unsuccessful CTO revascularization in a large cohort of patients. Methods: There were 1655 consecutive patients with at least one CTO included and were grouped into the successful revascularization (n=591) and unsuccessful revascularization (n=1064). Propensity score matching (PSM) was carried out to balanced clinical and angiographic characteristics. Cardiac mortality was defined as the primary endpoint. Major adverse cardiac event (MACE) was assessed as a “secondary endpoint”. Results: After 3.6 years follow-up, there was no significant difference between the successful and unsuccessful revascularization groups in the rate of cardiac mortality (adjusted hazard ratio [HR] 0.96, 95% confidence interval [CI] 0.59-1.58, p=0.865). After PSM analysis (371 pairs), between the two groups, cardiac mortality rate (HR 0.51, 95% CI 0.23-1.15, p=0.104) were equivalent, whereas the adjusted risk of MACE (HR 0.43, 95% CI 0.32-0.58, p=0.001) and target-vessel revascularization (HR 0.41, 95% CI 0.29-0.58, p<0.001) were significantly higher in patients with unsuccessful revascularization. Conclusion: For treatment of CTO patients, successful revascularization was not associated with a lesser risk for cardiac mortality as compared with unsuccessful revascularization. However, successful revascularization reduced MACE and target-vessel revascularization.